Pernapasan dalam Lambat (Slow Deep Breathing) sebagai Strategi Manajemen Gejala untuk Mengatasi Kelelahan (Fatigue) pada Pasien yang Menjalani Hemodialisis - Gina Maydinah; Lily Wahyuni Romadhon; Citra Setyo Dwi Andhini (STIKES Columbia Asia Medan, 2026)
Chronic Kidney Disease (CKD) is a chronic kidney condition characterized by progressive and irreversible decline in kidney function. CKD patients undergoing hemodialysis often experience fatigue due to anemia, accumulation of uremic toxins, and the prolonged duration of the hemodialysis process. Unresolved fatigue can reduce quality of life and the ability to perform daily activities. One nonpharmacological intervention that can be used to address fatigue is slow deep breathing therapy. The purpose of this study was to determine the application of slow deep breathing in CKD patients undergoing hemodialysis. This study used a qualitative approach, specifically a case study with a nursing care approach. The study subjects were two CKD patients. The therapy was administered using slow deep breathing techniques for 5 minutes, with 1–3 cycles, over three sessions. Data collection methods included interviews and observations. Data collection instruments comprised nursing assessment forms, head-to-toe physical examinations, and supporting data. After providing nursing care interventions over three sessions to the two patients, the results showed a reduction in complaints of weakness and fatigue; the patients appeared more relaxed and comfortable, and were better able to perform light activities.Slow deep breathing therapy as a nonpharmacological intervention to help reduce fatigue in CKD patients undergoing hemodialysis